PGC-1α activation to enhance macrophage immune function in mycobacterial infections - Joel R. Frandsen; Zhihong Yuan; Brahmchetna Bedi; Zohra Prasla; Seoung-Ryoung Choi; Prabagaran Narayanasamy; Ruxana T. Sadikot (PLoS ONE, 2025)
Nontuberculous Mycobacteria (NTM) are a heterogeneous group of environmental microorganisms with distinct human pathogenesis. Their incidence and prevalence are rising worldwide, due in part to elevated antimicrobial resistance which complicates treatment and potential successful outcomes. Although information exists on the clinical significance of NTMs, little is known about host immune response to infection. NTM infections alter macrophage mitochondrial capacity and decrease ATP production, efficient immune response, and bacterial clearance. Transcription factor peroxisome proliferator activated receptor (PPAR) γ coactivator-1α (PGC-1α) is a master regulator of mitochondrial biogenesis, influencing metabolism, mitochondrial pathways, and antioxidant response. Mitochondrial transcription factor A (TFAM) is a protein essential for mitochondrial DNA (mtDNA) genome stability, integrity, and metabolism. Both PGC-1α and TFAM regulate mitochondrial biogenesis and activity, and their disruption is linked to inflammatory signaling and altered macrophage function. We show that NTM causes macrophage mitochondrial damage and disrupted bioenergetics. Mechanistically we show that this is related to attenuation of expression of PGC-1α and TFAM in infected macrophages. Importantly, rescuing expression of PGC-1α and TFAM using pharmacologic approaches restored macrophage immune function. Our results suggest that pharmacologic approaches to enhance mitochondrial function provide a novel approach to target macrophage immune function and means to combat NTM infections.